Dokdo its history and facts - Kim, Hak-chun 1943- (Northeast Asian History Foundation, 2019)
"Dokdo has been an integral and inseparable part of Korean territory since ancient times. Throughout this book, the author attempted to prove this undeniable historical and geographical fact utilizing primary sources, thereby rejecting the Japanese claim that Dokdo is their territory. The author wishes this book would help the international community understand the true identity of Dokdo"--